Strategic Tax Competition in Switzerland: Evidence from a Panel of the Swiss Cantons - Lars P. Feld; Emmanuelle Reulier (Center for Research in Economics, Management and the Arts (CREMA), 2005)
Tax competition is discussed as a source of inefficiency in international taxation and in fiscal federalism. Two preconditions for the existence of such effects of tax competition are that mobile fac-tors locate or reside in jurisdictions with - ceteris paribus - lower tax rates and that taxes are actually set strategically in order to attract mobile production factors. It is well known from studies about Swiss cantonal and local income tax competition that Swiss taxpayers reside where income taxes are low. In this paper, empirical results on strategic tax setting by cantonal governments are presented for a panel of the Swiss cantons from 1984 to 1999. Completing the evidence on Swiss tax competition, the income tax rates in cantons are the lower, the lower are the tax rates of their neighbors.
Keywords: H71; H73; H24; 330; Tax competition; strategic tax setting; personal income taxes